AN ERROR ANALYSIS ON THE USE OF PERSONAL PRONOUNS IN DESCRIPTIVE WRITING MADE BY THE EIGHT GRADE STUDENTS OF SMP NURUL IMAN PALEMBANG, SOUTH SUMATERA - Muhamad Holandyah; Deta Desvitasari; Rizqy Dwi Amrina; Heru Saputra (JAMBI-ENGLISH LANGUAGE TEACHING, 2018)
English personal pronoun is one of difficult part of grammar English since it is different with Indonesian language. Each of personal pronoun has its own rules, so this case leads the students do some errors. The objectives of this research were to investigate the kinds of errors and the most dominant error on the use of personal pronouns in descriptive writing made by the eighth grade students of SMP Nurul Iman Palembang. This research designed as qualitative in the form of research. The subjects of this research were 37 eighth grade students which were chosen by using purposive sampling. To analyze the data, firstly, we collected the data from the students, and then we identified the errors by circling them, after that the researcher classified the errors by using Surface Strategy Taxonomy by Dulay, Burt and Krashen (1982), after that we calculated the data taken, and the last made the percentage in each category. The result showed that there were 128 items of errors found in student’s writing. The most dominant errors found in misformation with the percentage was 72.65% (93 errors). After that, omission errors found in students’ writing was 19.58% (25 errors), addition errors found was 7.81% (10 errors), and the last there was no error found in misordering.